Spanish poetry in 2006: traditions, stays and innovations (XXI Century. Spanish Literature and Culture, 2007)
This article focuses on the most noticeable works of published poetry within theSpanish literary milieu of 2007. In addition to examining the contributions of authorsalready established as innovators of their craft, it takes a look at several anthologies andhighlights the distinct tendencies that characterise the poetic evolution taking place inSpain today.
Keywords: poetry; Spanish poetry; tendencies